Pancreaticopleural Fistula as a Rare Cause of Both-Sided Pleural Effusion. (3rd March 2021) - Chmielecki, Jan; Kościński, Tomasz; Banasiewicz, Tomasz
Abstract : A pancreaticopleural fistula is a rare cause of pleural effusion. It is a complication of chronic or acute pancreatitis. It is rarely formed to the right or both pleural cavities. Diagnosis and proper treatment often turn out to be difficult and require the cooperation of a multidisciplinary team. The authors present the case of a 59-year-old patient treated for recurrent pleural effusion of unknown origin, first to the left and then to the right pleural cavity. After many months of treatment, the diagnosis of a pancreaticopleural fistula was made. The patient underwent surgery, which finally led to a successful complete recovery. Pancreaticopleural fistula should always be considered in patients with pleural effusion of unknown origin.